Pengaruh urbanisasi, tingkat kemiskinan, dan ketimpangan pendapatan terhadap kriminalitas di Provinsi Jawa Timur - Kuciswara, Dita; Muslihatinningsih, Fivien; Santoso, Edy (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2021)
This study aims to determine how big influence urbanization, poverty levels, and income inequality on criminality in East Java Province. The study used secondary data for 6 years, from 2014 to 2019. The data analysis method used in this study is the panel data regression method with the Fixed Effect Model (FEM) approach. The dependent variable used in this study is criminality, while the independent variables are urbanization, poverty level, and income inequality. Based on the results of this study, it can be concluded that urbanization has a positive and significant influence on criminality in East Java Province. The poverty rate has a positive and significant influence on criminality in East Java Province. Meanwhile, income inequality has a positive but insignificant effect on criminality in East Java Province.